Safety and Efficacy of Stereotactic Ablative Radiotherapy for Ultra-Central Lung Cancer - Wang, Bin; Dong, Yang; Yu, Xuyao; Li, Fengtong; Wang, Jingsheng; Chen, Huaming; Niu, Zeqian; Song, Yongchun; Yuan, Zhiyong; Tao, Zhen (Frontiers in Oncology, 2022)
Background: Ultra-central lung cancer (UCLC) is difficult to achieve surgical treatment. Over the past few years, stereotactic body radiotherapy (SBRT) obviously improved the clinical efficacy and survival of UCLC patients. However, the adapted scheme of radiation therapy is still controversial. For this, a single arm retrospective analysis was performed on UCLC patients treated with SBRT. Material and Methods: We retrospectively studied primary UCLC patients who were treated with SBRT of 56 Gy between 2010 and 2018. UCLC was defined as planning target volume (PTV) touching or overlapping the proximal bronchial tree, trachea, oesophagus, heart, pulmonary vein, or pulmonary artery within 2 cm around the bronchial tree in all directions. Results: A total of 58 patients whose median age was 68 years (range, 46-85) were included in our study, 79.3% of whom did not undergo any previous therapy. The median dose of the PTV was 77.8 Gy (range, 43.3-91.8), and the median PTV of tumors was 6.2 cm3 (range, 12.9-265.0). With a median follow-up of 57 months (range, 6-90 months), the median cumulative overall survival (OS) rate was 58 months (range, 2-105). In addition, the 1-year, 2-year and 5-year OS rates were 94.7%, 75.0% and 45.0%, respectively. In our univariable analysis (p=0.020) and multivariate analysis (p=0.004), the OS rate was associated with the PTV. The 5-year OS rates for PTV <53.0 cm3 and PTV ≥53.0 cm3 were 61.6% and 37.4%, respectively. Regarding toxicity after SBRT, there were two cases (3.5%) with grade ≥3 adverse events, of which 1 case died of sudden severe unexplained hemoptysis. Conclusions: Patients with UCLC can benefit from SBRT at a dose of 56 Gy. On the other hand, smaller PTV was associated with superior outcomes, and the cure difference needs to be validated by prospective comparative trials.